HUBUNGAN ANTARA JENIS PERSALINAN DENGAN KEBERHASILAN ASI EKSKLUSIF DI KECAMATAN BAKI KABUPATEN SUKOHARJO - Warsini Warsini; Sri Aminingsih; Rizky Ayu Fahrunnisa (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
Background Results of Indonesia Demographic and Health Survey (IDHS) in 2012 showed coverage exclusive breastfeeding in Indonesia have not been optimal, that was 42 %. This study was conducted to analyze the correlation between the kinds of giving births with the success of exclusive breastfeeding 6 (six) months.The subject and Methods The study was a quantitative analytic observational cross-sectional design. Large samples are 100 mothers who had babies aged 6-12 months. Sampling random sampling. Collecting data using questionnaires.The results showed that the average maternal age 20-35 years (80%), birth weight children mostly above 2,500 g (97%), maternal gestational age infants mostly pretty months (99%) and all infants the respondent was not born with congenital abnormalities, meaning that 100% of infants born with a normal weight difference, kinds of giving birth the mean of paravaginal (70%), the success rate of exclusive breastfeeding by 56%. Statistical shows that there is a positive correlation and statistically significant between the kinds of giving births with the success of exclusive breastfeeding (OR = 2.53 ; CI 95% 1.05 until 6.10 ; p = 0.035).Conclusion There was a significant correlation between the kinds of giving births with the success of exclusive breastfeeding.Keywords: the kinds of giving births, exclusive breastfeeding